Propuesta de implementación de un Glamping en la Comuna Zuleta, Sector Cocha Baja - Díaz Chuquín, Iván Mauricio (2023)
Tourism, as a socio-economic activity, plays a fundamental role in the development of various industries and communities at large. Emerging trends in this industry reflect a shift in the perception of travel, focusing on promoting more authentic experiences in harmony with nature. One of the most innovative proposals in Ecuador is Glamping, a fusion of 'glamour' and 'camping,' offering an accommodation experience that blends the comfort and luxury of a hotel with a close connection to nature. The main objective of this research was to develop a Glamping proposal in the community of Zuleta, located in the province of Imbabura. This initiative aims to boost tourism in the locality and capitalize on its rural environment, where indigenous cultures, native traditions, and picturesque landscapes, including lagoons and natural trails, coexist. Additionally, the study thoroughly analyzed the geographical, environmental, and cultural features of the area, as well as the structure of its tourism system. To achieve this goal, a mixed methodology was applied, primarily based on surveys and observation sheets. This strategy allowed for the collection of both qualitative and quantitative data. As a result of this analysis, it was concluded that potential customers are predominantly young adults with specific preferences regarding their lodging experience. It is concluded that the implementation of glamping is an innovative alternative that is gaining relevance in the community of Zuleta following emerging tourism trends.